KEANEKARAGAMAN NUSA TENGGARA TIMUR SEBAGAI PROVINSI PARIWISATA BERKELAS DUNIA - Hendrik Toda (Jurnal Administrasi Publik, 2017)
East Nusa Tenggara province is an island province composed of 22 districts and cities, there is a large diversity of natural resources scattered in almost all districts and cities. Contribution of the tourism sector in 2016 reached 2 trillion, with tourist arrivals of 90 thousand to 100 thousand visits per year. In May 2016, the tourism sector most visit is the District of Labuan Bajo where there is a Komodo Island as a tourist destination, Coastal Nemberala in Rote Ndao which has been crowned as The Most Popular Surfing Spot in Indonesia and the Sumba Island where there is a Nihi Watu which is a the world's best hotel version of international travel magazine: Travel and Leisure.Precisely dated 17 September 2016, NTT received the Pesona Indonesia 2016 award as the grand champion in tourism from ten categories contested. NTT successfully obtained three gold medals, one silver and one bronze.NTT as the province wich is currently developing Smart City program is expected to expand all the potential of it, especially in the world class tourism sector. This study use a method based on a literature review of theoretical studies related to Local Government Policy in developing the Smart City in the tourism sector.The literature review is expected to find a way or method to solves problems related to the areadevelopment and management of tourism. This will have an impact on local revenues, the region's development, the economy, local communities and the achievement of an increase in the number of tourists visiting NTT as the province who has the best travel Destinations in the world.